2019
DOI: 10.1073/pnas.1906388116
|View full text |Cite
|
Sign up to set email alerts
|

An in situ high-throughput screen identifies inhibitors of intracellular Burkholderia pseudomallei with therapeutic efficacy

Abstract: Burkholderia pseudomallei(Bp) andBurkholderia mallei(Bm) are Tier-1 Select Agents that cause melioidosis and glanders, respectively. These are highly lethal human infections with limited therapeutic options. Intercellular spread is a hallmark ofBurkholderiapathogenesis, and its prominent ties to virulence make it an attractive therapeutic target. We developed a high-throughput cell-based phenotypic assay and screened ∼220,000 small molecules for their ability to disrupt intercellular spread byBurkholderia thai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Although the T6SS is structurally well characterized and meets all the criteria as a promising virulence factor candidate, a very limited number of studies have attempted to develop anti-T6SS molecules or peptides. Certain studies have used phenotypic screening ( 58 ), and others have employed a targeted approach, such as blocking the interaction between the two sheath proteins (TssB and TssC) or the dissociation of a toxin immunity complex ( 28 , 59 ). Another study employed a nanobody intracellularly expressed to block the assembly of the membrane complex (MC) ( 60 ), which is limited in terms of a possible therapeutic application, since nanobodies cannot cross the bacterial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although the T6SS is structurally well characterized and meets all the criteria as a promising virulence factor candidate, a very limited number of studies have attempted to develop anti-T6SS molecules or peptides. Certain studies have used phenotypic screening ( 58 ), and others have employed a targeted approach, such as blocking the interaction between the two sheath proteins (TssB and TssC) or the dissociation of a toxin immunity complex ( 28 , 59 ). Another study employed a nanobody intracellularly expressed to block the assembly of the membrane complex (MC) ( 60 ), which is limited in terms of a possible therapeutic application, since nanobodies cannot cross the bacterial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque formation is the final scenario of infection in vitro that represents the virulence of intracellular B . pseudomallei [ 40 , 42 ]. This study demonstrated that B .…”
Section: Discussionmentioning
confidence: 99%
“…Plaque formation is a phenotypic characterization technique that is used as a surrogate for virulence of intracellular microbes such as Rickettsia rickettsii, Shigella flexneri, Listeria monocytogenes as well as B. pseudomallei and B. thailandensis [34][35][36][37][38][39][40][41]. Recently, plaque formation has been used as a high-throughput screen for inhibitors of the intracellular B. pseudomallei lifecycle [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telescope is capable of leveraging common and familiar technologies that do provide a user-friendly interface to manage jobs from any mobile device without compromising flexibility for advanced users. For example, Telescope allows users to track with their smartphones any bioinformatics tools (e.g., GATK 14 ) or jobs submitted by 4 specific platforms (e.g., Galaxy Project 14,15 ), displaying in real-time the partial outputs, warnings, and error messages associated with each job. Telescope includes the following functionality:…”
Section: Introductionmentioning
confidence: 99%